Colorimetria aplicada em pesquisa de madeira - Vetter, Roland E. (Acta Amazonica, 1988)
Color of wood and wood products can be determined by a reflectance reading filter colorimeter in which color is measured as a combination of three reflectance values - red, green and blue - reflected by the sample under defined conditions of illumination. The color of 58 Amazonian species has been determined based on standards of the German lnstitute of Standards (DIN).